Diversification Posture and Top Management Team Characteristics - Michel, John G.; Hambrick, Donald C. (Academy of Management Journal, 1992)
This study's argument is that a firm's diversification posture determines the degree of integration it needs across business units, which in turn influences the ideal composition of its corporate top management team. Archival data from 134 firms revealed that the degree of social cohesion and type of knowledge base within a firm's top management team were related to the degree of interdependence the firm's diversification posture demanded. Contrary to our hypotheses, experience in core functional areas among top team members was positively related to corporate performance in low-interdependence firms and negatively related to it in high-interdependence firms.